The Implementation of the Two Stay Two Stray Cooperative Learning Model to Improve the IPAS Learning Motivation of Grade IV Students at SD Inpres 12/79 Biru 1, Bone Regency - Anugrah Achmad Adiyaksa; Awaluddin Muin; Sidrah Afriani Rachman (Journal of Primary Education Innovation and Research, 2025)
This study is a classroom action research study that aims to improve the IPAS learning motivation of Grade IV students at SD Inpres 12/79 Biru 1, Bone Regency, through the Two Stay Two Stray cooperative learning model. The problem addressed in this study was the low learning motivation of students, as indicated by limited participation, attention, and interaction during the learning process, which was caused by the dominance of the lecture method and the limited opportunities for students to ask questions or express opinions. Data were collected through observation and questionnaires. The data analysis techniques in this study included data reduction, data presentation, and conclusion drawing. The results showed that students’ learning motivation in Cycle I indicated that 12 out of 20 students achieved the success indicators, with a percentage of 60% (Fair), whereas in Cycle II, 18 out of 20 students achieved the success indicators, with a percentage of 90% (Good). The percentage of teacher activity in Cycle I reached 76.19% (Fair), and in Cycle II it reached 90.47% (Good). The percentage of student activity in Cycle I reached 71.42% (Fair), and in Cycle II it reached 85.71% (Good). Thus, it can be concluded that the Two Stay Two Stray cooperative learning model is effective in improving the IPAS learning motivation of Grade IV students at SD Inpres 12/79 Biru 1, Bone Regency